Northeast Indian stalagmite records Pacific decadal climate change: Implications for moisture transport and drought in India. Issue 10 (19th May 2015) - Myers, Christopher G.; Oster, Jessica L.; Sharp, Warren D.; Bennartz, Ralf; Kelley, Neil P.; Covey, Aaron K.; Breitenbach, Sebastian F.M.
Abstract Two types of El Niño events are distinguished by sea surface temperature (SST) anomalies centered in the central or eastern equatorial Pacific. The Central Pacific El Niño events (CP‐El Niño) are more highly correlated with weakening of the central Indian Summer Monsoon and linked to decadal Pacific climate variability. We present a 50 year, subannually resolved speleothem δ18O record from northeast India that exhibits a significant correlation with northern Pacific decadal variability and central equatorial Pacific SSTs. Accordingly, we suggest that δ18O time series in similar northeast Indian speleothems are effective tools for investigating preinstrumental changes in Pacific climate, including changes in El Niño dynamics. In contrast to central India, rainfall amounts in northeast India are relatively unaffected by El Niño. However, back trajectory analysis indicates that during CP‐El Niño events moisture transport distance to northeast India is reduced, suggesting that variations in moisture transport primarily control δ18O in the region.